Peter Village and the delineation of space: new research at an unusual enclosure in central Kentucky - DeSanto, Carly M., author; Henry, Edward R., advisor; Van Buren, Mary, committee member; Choi, Jane, committee member; Carman, Scott, committee member (Colorado State University. Libraries, 2021)
After over a century of research, archaeologists still identify one of the most important characteristics of the Early and Middle Woodland Period in the Middle Ohio Valley region as the construction, maintenance, and use of small geometric ditch-and-embankment earthen enclosures. However, the Peter Village site (15Fa166), located in Fayette County, Kentucky, is a ditch-and-embankment earthen enclosure that is both non-geometric and unusually large. Past archaeological summaries of Peter Village have classified it as an example of a non-mortuary site in the region, though its exact purpose remains unknown. Recent archaeological research I conducted on this atypical enclosure includes analyses of LiDAR-derived topographic visualizations, subsurface geophysical surveys, soil cores, and the construction of a new radiocarbon chronology that employs Bayesian statistical modeling. The result of my work provides new insights into the delineation of space at Peter Village. My data indicate that a second, previously undefined, embankment likely exists exterior to the ditch. There is also evidence from my geophysical imagery that shows the enclosure's entrance and associated linear features in the southern, interior portion of the site. Finally, new radiocarbon data suggests that Peter Village is potentially one of the earliest examples of a ditch-and-embankment enclosure in the Middle Ohio Valley region. Using these new diverse datasets collected via multiple geoarchaeological methods, I argue that enclosure features like those present at Peter Village require us to reconsider their early monumental nature. Moreover, the identification of multiple embankments forces us to reconsider changes in the delineation of space at the site. Peter Village serves as an important example of how a multi-scalar archaeological investigation can expand upon previous archaeological research.
Keywords: archaeogeophysics; earthen monuments; monumentality; earthen enclosures; Adena; Eastern Woodlands